A strategic plan for Matina Gold Circle Shell Station - Digal, Mariel Ann O. (School of Management, University of the Philippines Mindanao, 2007)
Matina Gold Circle Shell Station is a full service gasoline station with a Forecourt Area, a Service Bay Area, and a select Convenience Store. It has been in existence for the past seven years. But it was only in 2004 that said dealership was transferred to its current dealer. Prior to transfer of dealership, the station had fallen into a state of disrepair and lost of sales due to the mismanagement of the previous dealer. The current dealer has poured in capital to refurbish the station's surroundings and for has enjoyed profitable operations in the three years of his dealership. However, the gasoline station industry is known for its low profit margins and the only way to ensure profitability is by increasing sales volume. This paper aims to formulate strategies for the said station to increase its profitability in light of the four direct competition identified namely: Flying V and three Petron gasoline stations. The analytical Framework of Dr. Tim Schramko from the University of Toledo was used in this strategic paper. This format consists of four steps as follows: input stage, matching stage, decision stage, and the output stage. The analytical tools employed in this framework are the EFE and IFE Matrix, SWOT Analysis, TOWS Matrix, and the QSPM. The proposed strategies are products of the study of the internal and external factors that concern Matina Gold Circle Shell Station. By using the analytical framework and the above-mentioned tools of analysis, the researcher identified three (3) strategies that may prove applicable to the station: Improving service quality by pushing for a distinctive image in the market, focusing efforts on personnel training and development, and increasing sales volume through specialization by customer type and focusing on their geographic area.